Tahsin and Tahfidz Learning System at Integrated Islamic Elementary School (SDIT) Insan Madani During the Pandemic Covid-19 - Afiful Ikhwan; Saiful Anwar; Nashikhatun Mahmudah (Al-Hayat: Journal of Islamic Education, 2021)
Integrated Islamic Primary School (SDIT) Insan Madani Madiun has implemented online learning in the Even Semester of the 2019/2020 Academic Year to keep the learning going during the Covid-19 pandemic. This study aims to analyze the learning process of tahsin and tahfidz during the Covid-19 pandemic. This type of research is descriptive qualitative; indirect interviews carried out data collection due to the effects of the Covid-19 pandemic. This study indicates that learning uses existing social media with a system, namely the provision of learning videos, then students make daily Tahsin and Tahfidz deposits via WhatsApp (WA). Some of the obstacles include consuming a lot of quotas and weak internet networks. The learning process still needs to be optimized, and it is necessary to evaluate the improvement of online learning in the next period.